THE EFFECT OF USING JIGSAW TECHNIQUE ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 7 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Ima Dayanti; Jismulatif Jismulatif; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to find out the effect of using Jigsaw techique on the ability of the first year students of SMAN 7 Pekanbaru in comprehending narrative texts. This study was one group pre-test and post-test design. The population of this study was the first year students of SMAN 7 Pekanbaru which consisted of 7 classes with the total of 238 students. The sample of this study was X.4 class with 35 students. The writer, during treat the students, found that students’ motivation to read the text increase. Besides, students got more confidences to split out their opinion while discussion and present the result in front of the class. After treatment was held, the writer distributed the tests. The instrument of the research was a reading test with multiple choice type. The result showed a strong correlation between Jigsaw technique and students’ reading comprehension. Tobs result also showed that the students’ mean score of the post-test (75.89) was higher than the pre-test (64.74). Besides, the results of the analysis showed that the t-test was higher than the ttable (2.704<15.191>1.684) at the level sig. of 0.01 and 0.05 with the degree of freedom (df) n-1=34. Based on the data calculation, the results showed the effects of using Jigsaw technique on the ability of the first year students of SMAN 7 Pekanbaru in comprehending narrative texts. Based on the result of this study, the writer over some suggestions. For the teacher, they are expected to arrange the teaching and learning process well in order to make students more active and gives respond well to the material. This study also useful for students. Students are expected to study more and respond in learning process. At last, for the next researcher, they are expected to improve and solve the problems that the researcher does not achieve at this time.Keywords: Jigsaw, Reading Comprehension, Narrative Text